Physical Exercise and Mitochondrial Disease: Insights From a Mouse Model - Fiuza-Luces, Carmen; Valenzuela, Pedro L.; Laine-Menéndez, Sara; Fernández-de la Torre, Miguel; Bermejo-Gómez, Verónica; Rufián-Vázquez, Laura; Arenas, Joaquín; Martín, Miguel A.; Lucia, Alejandro; Morán, María (Frontiers in Neurology, 2019)
Purpose: Mitochondrial diseases (MD) are among the most prevalent neuromuscular disorders. Unfortunately, no curative treatment is yet available. This study analyzed the effects of exercise training in an animal model of respiratory chain complex I deficiency, the Harlequin (Hq) mouse, which replicates the clinical features of this condition. Methods: Male heterozygous Harlequin (Hq/Y) mice were assigned to an ‘exercise’ (n=10) or a ‘sedentary’ control group (n=11), with the former being submitted to an 8-week combined exercise training intervention (aerobic+resistance training performed five times/week). Aerobic fitness, grip strength, and balance were assessed at the beginning and at the end of the intervention period in all the Hq mice. Muscle biochemical analyses (with results expressed as percentage of reference data fom age/sex-matched sedentary wild-type mice [n=12]) were performed at the end of the aforementioned period for the assessment of major molecular signaling pathways involved in muscle anabolism (mTOR activation) and mithocondrial biogenesis (proliferator activated receptor gamma coactivator 1α [PGC-1α] levels), and enzyme activity and levels of respiratory chain complexes, and antioxidant enzyme levels. Results: Exercise training resulted in significant improvements in aerobic fitness (-33±13m and 83±43m for the difference post- vs pre-intervention in total distance covered in the treadmill tests in control and exercise group respectively, p=0.014) and muscle strength (2±4g vs 17±6g for the difference post vs pre-intervention, p=0.037) compared to the control group. Higher levels of ribosomal protein S6 kinase beta-1 phosphorylated at threonine 389 (156±30% vs 249±30%, p=0.028) and PGC-1α (82±7% vs 126±19% p=0.032) were observed in the exercise-trained mice compared with the control group. A higher activity of respiratory chain complexes I (75±4% vs 95±6%, p=0.019), III (79±5% vs 97±4%, p=0.031) and V (77±9% vs 105±9%, p=0.024) was also found with exercise training. Exercised mice presented with lower catalase levels (204±22% vs 141±23%, p=0.036). Conclusion: In a mouse model of MD, a training intervention combining aerobic and resistance exercise increased aerobic fitness and muscle strength, and mild improvements were found for activated signaling pathways involved in muscle mitochondrial biogenesis and anabolism, OXPHOS complex activity, and redox status in muscle tissue.